2013
DOI: 10.2147/ijn.s42242
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell-mediated hepatic injury induced by silica nanoparticles in vitro and in vivo

Abstract: Silica nanoparticles (SiO 2 NPs) have been shown to exert cytotoxic effects in hepatocytes and to cause liver injury. In the liver, Kupffer cells (KCs), as the resident macrophages, play an important role in the normal physiology and homeostasis of the liver. Nevertheless, few studies have attempted to clarify the role of KCs in hepatic injury induced by SiO 2 NPs. In this study, we treated Buffalo rat liver (BRL) cells with the supernatants of SiO 2 NP-stimulated KCs to determine KC-mediated hepatotoxicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 43 publications
(38 reference statements)
3
25
0
Order By: Relevance
“…The transient increase in ROS levels and activation of Nrf2 transcription factor for TiO 2 and to a lesser extent PAA correlates with the highest cytotoxicity of these two NPs and is in agreement with other studies, where it has been shown that TiO 2 and iron oxide NPs can induce apoptosis and other changes in vitro through ROS-mediated mechanisms [ 73 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. Furthermore, mild oxidative stress activates phase II antioxidant enzymes through the activation of Nrf2 transcription factor, while high levels of ROS overwhelm a cell’s protective mechanisms and cause cell dysfunction and cell death [ 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…The transient increase in ROS levels and activation of Nrf2 transcription factor for TiO 2 and to a lesser extent PAA correlates with the highest cytotoxicity of these two NPs and is in agreement with other studies, where it has been shown that TiO 2 and iron oxide NPs can induce apoptosis and other changes in vitro through ROS-mediated mechanisms [ 73 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. Furthermore, mild oxidative stress activates phase II antioxidant enzymes through the activation of Nrf2 transcription factor, while high levels of ROS overwhelm a cell’s protective mechanisms and cause cell dysfunction and cell death [ 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…Further, KCs stimulated with NMs secreted significant quantities of the pro-inflammatory cytokine TNF-α. Chen, Xue, and Sun (2013) also showed that supernatants of the KCs stimulated with SiO 2 NMs, subsequently reduced cellular viability in BRL cells.…”
Section: Introductionmentioning
confidence: 85%
“…Further, buffalo rat liver (BRL) cells were treated with supernatants derived from SiO 2 NM-stimulated KCs (isolated primary cells) (in vitro 24 hr exposure at a concentration range of 100-800 μg/ml) to determine KC-mediated hepatotoxicity. Chen, Xue, and Sun (2013) showed as compared with control NMs-induced inflammatory cell infiltration at the portal regions of the liver. In addition, exposure of rats to SiO 2 NMs for 48 hr resulted in a significant rise in the number of KCs in the tissue.…”
Section: Introductionmentioning
confidence: 87%
“…The QDs entered the liver through the venous pathway and then first came into contact with macrophages and sinusoidal endothelial cells in the liver (Liang et al, 2015). Kupffer cells play a very important role in mediating the liver toxicity of QDs, and the intake of QDs in to Kupffer cells will greatly affect the toxic effects of QDs on other hepatocytes (Chen, Xue, & Sun, 2013;Fischer et al, 2010;Liang et al, 2015;Zhu et al, 2017). The Liang et al study showed that CdTe/CdS-MSA QDs mainly accumulated in the liver sinusoids and were selectively taken up by Kupffer cells and liver sinusoidal endothelial cells instead of by hepatocytes within 3 h (Liang et al, 2015).…”
Section: Other Factorsmentioning
confidence: 99%